2021
DOI: 10.1007/s40744-021-00324-w
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolic Acid Exposure Optimization Based on Vitamin D Status in Children with Systemic Lupus Erythematosus: A Single-Center Retrospective Study

Abstract: Introduction: Systemic lupus erythematosus (SLE) can affect bone metabolism and homeostasis of serum electrolytes that are associated with abnormal levels of vitamin D. Mycophenolate mofetil (MMF) is a commonly used immunosuppressant with the active metabolite mycophenolic acid (MPA). The area under the plasma concentration-time curve (AUC) of MPA is often monitored during the treatment to assess the exposure levels. This study aims to explore the association between exposure levels of MPA and 25-hydroxyvitami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Ye et al [96] observed increased levels of MPA exposure with decreased incidence odds of diabetes, acute kidney injury, or pneumonia and proposed even higher target exposure levels of MPA AUC for clinical practice (100.39 and 50.20 mg•h/L for AUC 0-24 and AUC 0-12 , respectively) in systemic lupus erythematosus children. In other study, Ye et al [94] suggested that target exposure levels might amount to 98.71 and 49.36 mg•h/L for AUC 0-24 and AUC 0-12 , respectively. Chen et al [92] evaluated target MPA pharmacokinetic parameters using different analysis and criteria and found that in studied children, an AUC 0-12 threshold of 39 µg•h/mL or a C trough of 1.01 µg/mL was associated with the lowest risk of active disease (ROC analysis), whereas an AUC 0-12 of <34 µg•h/mL or a C trough <1.2 µg/mL (logistic regression analysis) might be associated with active disease.…”
Section: Tdm Based On Pharmacokineticsmentioning
confidence: 92%
See 2 more Smart Citations
“…Ye et al [96] observed increased levels of MPA exposure with decreased incidence odds of diabetes, acute kidney injury, or pneumonia and proposed even higher target exposure levels of MPA AUC for clinical practice (100.39 and 50.20 mg•h/L for AUC 0-24 and AUC 0-12 , respectively) in systemic lupus erythematosus children. In other study, Ye et al [94] suggested that target exposure levels might amount to 98.71 and 49.36 mg•h/L for AUC 0-24 and AUC 0-12 , respectively. Chen et al [92] evaluated target MPA pharmacokinetic parameters using different analysis and criteria and found that in studied children, an AUC 0-12 threshold of 39 µg•h/mL or a C trough of 1.01 µg/mL was associated with the lowest risk of active disease (ROC analysis), whereas an AUC 0-12 of <34 µg•h/mL or a C trough <1.2 µg/mL (logistic regression analysis) might be associated with active disease.…”
Section: Tdm Based On Pharmacokineticsmentioning
confidence: 92%
“…MPA TDM is recommended in pediatric patients, but it is still not a routine practice although numerous studies proved the advantage of dose adjustment based on TDM [66][67][68][69][70][71][72][73]. Our review includes studies on the MPA TDM in children after renal transplantation [67,[74][75][76][77][78][79][80][81], other organ transplantation such as heart [82,83], liver [72], or intestine [65], children after hematopoietic stem cell transplantation [84][85][86][87][88][89] or cord blood transplantation [90], and children with lupus [71,73,[91][92][93][94][95][96], nephrotic syndrome [69,70,[97][98][99][100][101][102][103][104][105]…”
Section: Mpa Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nrf2 inhibits Th17 differentiation and reduces STAT3 phosphorylation by upregulating Socs3 expression ( Figure 6 ) [ 141 ]. SLE can affect bone metabolism and serum electrolysis through renal impairment and by disturbing endocrine homeostasis [ 142 ]. In general, dysimmunity, oxidative stress, and inflammation are the key pathogenic features of SLE and LN [ 143 , 144 ].…”
Section: Research Progress Of Nrf2 In Inflammation-related Diseasesmentioning
confidence: 99%